Unconfined compressive strength of clay soils at different temperatures: experimental and constitutive study - Mohammadi, Fariborz; Maghsoodi, Soheib; Cheshomi, Akbar; Rajabi, Ali M. (Environmental earth sciences, 2022)
Unconfined compressive strength ( S u ) is one of the soil engineering parameters used in geotechnical designs. Due to the temperature changes caused by some human activities, it is important to study the changes in S u at different temperatures. On the other hand, due to the differences in the mineralogical composition of clay soils, it is important to study this subject in different clays. For this purpose, kaolin, illite and montmorillonite clays with a liquid limit (LL) of 47, 80 and 119, were tested in a temperature-controlled cell in temperature range of 20 to 60 ∘ C. Temperature was applied in undrained conditions and the results showed that the pore water pressure was a function of temperature and by heating, it increased in the samples. For specific temperature pore water pressure generated in montmorillonite was higher than Illite and kaolin. In all three types of clay, the S u decreased linearly with increasing temperature. The reduction of S u in kaolin was more than illite and in illite was more than montmorillonite. For all three samples, with increasing temperature, the modulus of elasticity (E) decreased non linearly. Increasing the temperature reduced strength and the stiffness of the clay samples.. The results of unconfined compressive tests at different temperatures were simulated using hypoplastic model. Impact of temperature was replicated by the model.